Clinical Utility of Jugular Venous Blood Gas Biomarkers for Assessing Traumatic Brain Injury Severity and Predicting ICU Stay Duration: A Biochemical and Predictive Modeling Approach: JVBG in Cranial Brain Injury - Qi, Bin; Du, Wenjie; Zhang, He; Jiang, Yuhui; Zhuo, Ming; Xu, Haixia (Journal of Medical Biochemistry, 2025)
Background: Biochemical monitoring of cerebral oxygen metabolism is essential in the management of traumatic brain injury (TBI). Jugular venous blood gas (JVBG) analysis provides real-time data reflecting cerebral biochemical states, offering a valuable window into brain oxygenation and metabolic demands. This study aimed to evaluate JVBG biochemical markers as indicators of TBI severity and as predictors of prolonged intensive care unit (ICU) stay, emphasizing their integration into machine learning models for clinical utility.Methods: A retrospective analysis was conducted on 100 ICU-admitted TBI patients. Serial measurements of JVBG parameters—jugular venous oxygen saturation (SjvO₂), partial pressure of oxygen (PjO₂), arteriovenous oxygen difference (AVDO₂), and oxygen content difference (AVDL)—were performed over five days. Spearman correlation and random forest algorithms were employed to assess relationships between JVBG biomarkers, clinical severity (via Glasgow Coma Scale), and ICU duration.Results: Patients with more severe TBI exhibited significantly reduced SjvO₂ and PjO₂, and elevated AVDO₂ and AVDL (p < 0.001). Strong correlations were found between JVBG markers and clinical severity scores. A multivariable prediction model incorporating age, SaO₂, and PaCO₂ at one day post-admission yielded excellent predictive performance for prolonged ICU stay (AUC = 0.974; sensitivity = 100%; specificity = 94.8%).Conclusion: JVBG biomarkers serve as clinically informative biochemical indicators for assessing TBI severity and forecasting ICU duration. Their integration into predictive algorithms may enhance precision in neurocritical care and support biochemical decision-making in intensive care settings.
Keywords: Jugular venous blood gas; traumatic brain injury; cerebral oxygenation; biochemical markers; ICU prediction; machine learning